Device modification of field-effect transistor PH sensor towards improved sensitivity / Khairul Aimi Yusof - Yusof, Khairul Aimi (2019)
This thesis presents the device modification of FET based pH sensors, namely ion-sensitive FET (ISFET) and extended-gate FET (EGFET) based sensors, to achieve good device performance. The first part of this research focused to improve the light sensitivity effect of ISFET. Two approaches of layout design modifications have been designed, fabricated, and measured. The first approach was designing a layout and fabrication of three different source-drain metal shield. The findings revealed that by implementing the metal shield layer modification, a good reduction of light sensitivity effect reduced to around 50% and the percentage of leakage current also decreased for about 52.29 % compared to without metal shield at source-drain area. Meanwhile, the source-drain metal shield paired with LOCOS isolation modification has been presented for the second approach. The results successfully indicated excellent reduction on the light sensitivity effect down to 96 % and the leakage current also reduce to 95.21 % compared to that of without metal shield at source-drain area and LOCOS. Then, completed packaged sensor with reduction techniques revealed that the pH sensitivity and linearity at dark environment were 50.17 mV/pH and 0.99997, respectively, whereas, at light environment were obtained at 50.83 mV/pH and 0.99997 respectively. Hence, it proves that the light sensitivity effect reduction technique which the layout of source-drain metal shield with LOCOS isolation modification that imply at this pH sensor managed to overcome the light effect issue. Next, to further improve the sensor sensitivity, the alternative materials were studied, namely TiO2 and Ta2O5 by implementing EGFET configuration due to simple and easy in fabrication and packaging of the sensing membrane part. EGFET pH sensor performances were studied using different materials of sensing films, different fabrication techniques, and also testing and characterization of EGFET pH sensor. The overall findings in studies of exploring suitable materials and fabrication techniques revealed that Ta2O5 sensing film prepared at lower RF power of 100 W gives excellent pH sensing properties with higher pH sensitivity (58.70 mV/pH), good linearity (0.99673), smaller hysteresis voltage for both acid and alkaline pH loops (1.24 mV and 3.45 mV), and a lower drift rate (0.1935 mV/h), relative to those of the system that had been subjected to other materials. Then, the best parameter of Ta2O5 thin film with higher pH sensitivity was applied in order to further extend the investigation of the semiconductor device characterizations. The results showed that the sputtered thin film gives higher pH sensitivity and linearity, small hysteresis and drift, and good repeatability, and reproducibility.